Impactos do tipo de controle dos inversores da microgeração fotovoltaica na rede de distribuição - Gonçalves, Bruno Canesso (2018)
Currently, the vast major of utility distribution companies around the globe require frequency inverters connected to the power grid to operate with unit power factor. However, due to the increase in presence of distributed generation (DG), it’s been discussed the role of DGs in the daily operation of the grid, using different types of control of the frequency inverters. Based on these new assignments to this equipment, this work has as subject the evaluation of the impacts of different types of control of microgeneration photovoltaic frequency inverters on distribution power networks, by monitoring certain performance indices, such as voltage levels, transformers loading and active power losses. Four types of control are considered, all analyzed at different levels of photovoltaic penetration. The software SIMULIGHT is used to perform the static and dynamic studies using the modified IEEE 34 bus feeder, by applying typical load and photovoltaic curves whereas clear sky.